Relationship between Anxiety and Breastfeeding Self-Efficacy in Post Partum Mothers after Sectio Caesarea (Sc) at dr. Sudirman Kebumen - Maryani, Desty; Riyanti, Eka; Astutiningrum, Diah; Herniyatun, H (Prosiding University Research Colloquium, 2022)
Delivery through Sectio caesarea (SC) operation is one of the increasing prevalence events in the world. The psychological impact on women post Sectio caesarea (SC) is fear and anxiety if the analgesic is lost, the pain will be felt. This anxiety is one of the factors that affect the mother's self-efficacy in breastfeeding. Objective: to determine the relationship between anxiety and breastfeeding self-efficacy in postpartum mothers after Sectio caesarea (SC) at Dr. Soedirman Kebumen. Methods: The research method is correlational with a cross-sectional approach. The population taken in this study were postpartum mothers post Sectio caesarea (SC) a total of 1,032 people. The research sample was 91 respondents who were taken by purposive sampling. The tool in this research is a questionnaire. Data were analyzed descriptively and correlatively. Result : Post-Section Caesarea (SC) postpartum women at RSUD Dr. Soedirman in the category of moderate anxiety (81.3%). Post-sectional caesarea (SC) mother at RSUD Dr. Soedirman in the category of high Breastfeeding Self Efficacy (52.7%). There is a relationship between anxiety and breastfeeding self-efficacy in postpartum mothers after Sectio caesarea (SC) at Dr. Soedirman Kebumen (p = 0.006).